2021
DOI: 10.1371/journal.pone.0261900
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological safety of VOHO Hemp Oil; a supercritical fluid extract from the aerial parts of hemp

Abstract: VOHO Hemp Oil (Verdant Nature LLC (in collaboration with HempFusion)) is an extract of the aerial parts of hemp (Cannabis sativa L) manufactured using a supercritical CO2 extraction process. The results of four safety studies are reported here including a bacterial reverse mutation assay, an in vivo mammalian micronucleus study, a maximum tolerated dose study in rats and a 90-day repeat dose subchronic toxicity study in rats. VOHO Hemp oil can contain up to 30% phytocannabinoids and less than 0.2% is tetrahydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 10 publications
2
22
1
Order By: Relevance
“…From the studies assessed by EFSA [7], only 3 animal studies were identified with suitable dose-response data for benchmark dose modelling, and additionally a study of Dziwenka et al [9] was included. Two of the studies (GWTX1412 and GWTX1413) were published in the context of the approval process of the CBD medicinal product Epidiolex as part of the application review files on the US Food and Drug Administration (FDA) website [13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the studies assessed by EFSA [7], only 3 animal studies were identified with suitable dose-response data for benchmark dose modelling, and additionally a study of Dziwenka et al [9] was included. Two of the studies (GWTX1412 and GWTX1413) were published in the context of the approval process of the CBD medicinal product Epidiolex as part of the application review files on the US Food and Drug Administration (FDA) website [13].…”
Section: Resultsmentioning
confidence: 99%
“…As the extract was of a comparably high purity of CBD, the authors decided to still include the study for comparative reasons. Similarly, Dziwenka et al [9,15] recently provided 2 studies of hemp extracts; while the 2020 study [15] did not provide raw data necessary for BMD modelling, the 2021 study [9] was included for comparative reasons as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data analysed in this study were obtained from the statement of the EFSA NDA panel [7]. No additional searches for data were conducted, apart from inclusion of another informative study of Dziwenka et al [9] not included in the EFSA statement [7].…”
Section: Methodsmentioning
confidence: 99%